Saint Martin's guide to writing - Axelrod, Rise B (Bedford/St. Martin's, 2008)
Includes indexes; The book can serve as a comprehensive introduction to nine genres of writing. It prepares the students for the kinds of writing specific to academic discourse It has examples for specific kind of writing which helps you to write your own essays